Classification of Environmental Strategies by Corporations - Saleem, Farida (Journal of Ecohumanism, 2024)
The current study aims to develop a framework for corporations’ classification of environmental strategies. Stakeholder theory and institutional approach are used to identify internal and external pressures that organizations face regarding environmental response. Based on the review of the literature, different classifications of environmental strategies were identified. A holistic matrix of corporate environmental response is developed on a continuum of low to high pressures from internal factors and external factors. The classification of environmental strategies based on internal and external pressures illustrates the complexity of organizational responses to environmental challenges. Companies can adopt a mix of proactive, compliance-oriented, and hybrid strategies to address both internal goals and external expectations effectively